2021
DOI: 10.14744/semb.2021.87160
|View full text |Cite
|
Sign up to set email alerts
|

Patient Eligibility for Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA) in an Endemic Region

Abstract: Objective: Transoral endoscopic thyroidectomy vestibular approach (TOETVA) is a scarless method that enables thyroidectomyusing natural orifice of the body. The opinion which is even common among TOETVA performing surgeons is that this surgery involves a small percentage of thyroidectomy applied patients. In this study, based on the currently accepted exclusion criteria, we aimed to determine what percentage of patients, who underwent thyroidectomy in an endemic area are actually suitable for TOET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For TOETVA, the generally accepted maximum size for benign nodules is <5 to 6 cm, with a thyroid volume typically below 45 mL 27–30 . However, in the case of Graves patients, we believe the acceptable thyroid volume for TOETVA is usually smaller than that for nodular disease due to the thyroid’s fragility, hypervascularity, and associated risks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For TOETVA, the generally accepted maximum size for benign nodules is <5 to 6 cm, with a thyroid volume typically below 45 mL 27–30 . However, in the case of Graves patients, we believe the acceptable thyroid volume for TOETVA is usually smaller than that for nodular disease due to the thyroid’s fragility, hypervascularity, and associated risks.…”
Section: Discussionmentioning
confidence: 94%
“…For TOETVA, the generally accepted maximum size for benign nodules is <5 to 6 cm, with a thyroid volume typically below 45 mL. [27][28][29][30] However, in the case of Graves patients, we believe the acceptable thyroid volume for TOETVA is usually smaller than that for nodular disease due to the thyroid's fragility, hypervascularity, and associated risks. If the thyroid volume exceeds the surgeon's experience-based threshold, we discuss it with the patient and recommend open surgery for safety reasons.…”
Section: Discussionmentioning
confidence: 97%
“…(8) The primary indication for TOETVA is improved cosmesis but this 'soft' primary outcome should not deter practitioners from developing skills which offer better cosmetic outcomes. (1,4,5) As part of this process, emphasis will be placed on understanding the impact of the new procedure on the incidence of complications usually associated with traditional thyroid surgery such as recurrent laryngeal nerve injury, permanent hypoparathyrodism and post-operative haemorrhage. In addition, efforts are made to mitigate the incidence of speci c complications, such as infection, mental nerve injury and mentalis dysfunction and rate of conversion.…”
Section: )mentioning
confidence: 99%
“…(2) As for other procedures, there will be a learning curve, additional costs and operative time. (5,(9)(10)(11)(12). Reassuringly, a recent metanalysis of six eligible nonrandomized studies involving 1151 patients revealed that TOETVA group had a signi cantly longer operative time but there were no signi cant differences in terms of postoperative outcomes.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation